Strategi Pengembangan Budidaya Lele Dumbo melalui Analisis SWOT–QSPM di Desa Wates Nganjuk - Ika Puspitasari Dyah Rahmadhani; Tiara Ayu Nugraha Putri (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
The catfish (Clarias gariepinus) farming business in Wates Village demonstrates significant economic potential, supported by increasing market demand. Catfish production data in Nganjuk District indicates a growth trend of 11% from 2021 to 2023. Contributing factors include relatively short harvest cycles, high production levels, and simple cultivation and maintenance processes, which have attracted a growing number of entrepreneurs to enter this sector. However, despite these advantages, the catfish farming industry faces several internal and external challenges. Internally, farmers encounter problems such as water quality management and the spread of fish diseases. Externally, they must contend with market price fluctuations, limited digital access, and inadequate infrastructure. These conditions highlight the need for a comprehensive strategic study to guide sustainable development in the catfish farming sector. This study aims to identify and analyze internal factors, strengths and weaknesses, as well as external factors, opportunities and threats, that influence the success of catfish farming in Wates Village. The research was conducted in February 2025 using purposive sampling, involving five teenage respondents selected from catfish farming businesses. The scope focuses on aspects of production management, environmental conditions, and market access strategies. To determine strategic priorities, the study employs a combination of the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and the Quantitative Strategic Planning Matrix (QSPM) method. Data were collected through field observations, in-depth interviews with business actors, and document reviews. The results indicate that the top strategic priority, with the highest Total Attractiveness Score (TAS) of 5.54, is the implementation of a filtration system and regular water quality monitoring. In addition, the implementation of biosecurity measures and the optimization of digital-based distribution channels can support the applied development strategy. This research is expected to serve as a reference for entrepreneurs and policymakers in designing competitive and sustainable catfish farming development strategies.